2010
DOI: 10.1614/ws-d-09-00066.1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Water Potential as Parameters for Modeling Weed Emergence in Central-Northern Italy

Abstract: Predicting weed emergence dynamics can help farmers to plan more effective weed control. The hydrothermal time concept has been used to model emergence as a function of temperature and water potential. Application of this concept is possible if the specific biological thresholds are known. This article provides a data set of base temperature and water potential of eight maize weeds (velvetleaf, redroot pigweed, common lambsquarters, large crabgrass, barnyardgrass, yellow foxtail, green foxtail, and johnsongras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 36 publications
8
77
0
Order By: Relevance
“…The range of t b values estimated for a. theophrasti (3.5 ± 1.15°C to 4.9 ± 0.16°C) was in complete agreement with the results of previous studies on an Iranian population (Sadeghloo et al 2013), but also on European populations (Masin et al 2010;Loddo et al 2013), while Dorado et al (2009b) reported a value of around 7°C as t b for a Spanish population. Results obtained for a. albus (t b from 10.4 ± 0.42°C to 13.1 ± 0.46°C) confirmed previous findings by Steckel et al (2004), who observed almost no germination for this species at 10°C, while higher values of t b , ranging from 14°C to 17°C, were estimated by Steinmaus et al (2000).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The range of t b values estimated for a. theophrasti (3.5 ± 1.15°C to 4.9 ± 0.16°C) was in complete agreement with the results of previous studies on an Iranian population (Sadeghloo et al 2013), but also on European populations (Masin et al 2010;Loddo et al 2013), while Dorado et al (2009b) reported a value of around 7°C as t b for a Spanish population. Results obtained for a. albus (t b from 10.4 ± 0.42°C to 13.1 ± 0.46°C) confirmed previous findings by Steckel et al (2004), who observed almost no germination for this species at 10°C, while higher values of t b , ranging from 14°C to 17°C, were estimated by Steinmaus et al (2000).…”
Section: Discussionsupporting
confidence: 90%
“…This procedure ensured the photostimulation necessary to promote seed germination since the studied species, as many other weeds, are very sensitive even to short light exposures as that occur during soil tillage (Batlla & Benech-Arnold 2014). Seeds were incubated at a series of constant temperatures (6, 8, 10, 12, 14, 16, 18, 20, 24, 28, and 32°C), chosen according to previous experiments conducted on different species (Steinmaus et al 2000;Steckel et al 2004;Masin et al 2010). These temperatures are within the range of suboptimal temperatures for germination of the studied species.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations